2014
DOI: 10.1371/journal.pone.0107771
|View full text |Cite
|
Sign up to set email alerts
|

Developing Item Banks for Measuring Pediatric Generic Health-Related Quality of Life: An Application of the International Classification of Functioning, Disability and Health for Children and Youth and Item Response Theory

Abstract: The purpose of this study was to develop item banks by linking items from three pediatric health-related quality of life (HRQoL) instruments using a mixed methodology. Secondary data were collected from 469 parents of children aged 8-16 years. The International Classification of Functioning, Disability and Health-Children and Youth (ICF-CY) served as a framework to compare the concepts of items from three HRQoL instruments. The structural validity of the individual domains was examined using confirmatory facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Comparing HRQoL measures with the ICF may reveal its uniqueness, demonstrating the nature and scope of its content. In most cases, instruments focus on different aspects of ICF domains, with "body functions" and "activities and participation" components usually predominating (7,8). In the 4 versions presented here (CFQ parents6-13 ; CFQ 6-11 ; DISABKIDS self ; and DISABKIDS proxy ), the categories primarily represented body functions, except for the CFQ 6-11 , version, where the activities and participation component was the most frequent.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparing HRQoL measures with the ICF may reveal its uniqueness, demonstrating the nature and scope of its content. In most cases, instruments focus on different aspects of ICF domains, with "body functions" and "activities and participation" components usually predominating (7,8). In the 4 versions presented here (CFQ parents6-13 ; CFQ 6-11 ; DISABKIDS self ; and DISABKIDS proxy ), the categories primarily represented body functions, except for the CFQ 6-11 , version, where the activities and participation component was the most frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the clinical manifestations present in the scope of body functions resulting from the multisystemic nature of CF, the questionnaires can be used to address a large number of aspects related to this domain (7,8,19). Studies that seek to identify clinical factors associated with HRQoL in individuals with CF have concluded that variables assessing exacerbation and pulmonary function have the greatest impact on HRQoL (4,20,21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations